Pengalaman Vietnam Melakukan Transplantasi Hukum: Persaingan Terhadap Kondisi Domestik Setempat - Isharyanto Isharyanto (Fakultas Hukum Universitas Islam Indonesia, 2020)
This paper describes the problems and challenges as the effects of legal transplantation. As a policy alternative, legal transplantation is an appropriate short-term solution to immediately produce a new legal formulation. This study focuses on analyzing the characters of legal transplant in Vietnam which reflects the competition in local domestic conditions. This doctrinal legal research uses both conceptual and historical approach. The conceptual approach refers to the issue of legal transplantation while the historical approach refers to the historical course of law in Vietnam. Conclusively, in Vietnam's experience, the results of a legal transplant did not take place smoothly and immediately. The footprint of the legal transition and the combination of traditional order with the influence of colonial inheritance law causes the transplantation effect to not immediately contribute to positive conditions for legal development. Apart from the rigid communist system, which accommodates a market-friendly liberal economic system, the need for regulation in accordance with the development of contemporary social relations arises. However, party interference, including in controlling judges and courts, causes mixed forms of legal transplantation that have no equivalent in the mainstream legal system. Transplanted law in Vietnam does not only present a new face to the law and court system, but also influences the challenges of future development so that the transplantation effect can contribute to positive steps for legal reform.